The EuroSIDA study: 25 years of scientific achievements. Issue 2 (24th October 2019) - Laut, K; Kirk, O; Rockstroh, J; Phillips, A; Ledergerber, B; Gatell, J; Gazzard, B; Horban, A; Karpov, I; Losso, M; d'Arminio Monforte, A; Pedersen, C; et al.
Abstract : The EuroSIDA study was initiated in 1994 and follows adult people living with HIV (PLHIV) in 100 collaborating clinics across 35 countries covering all European regions, Israel and Argentina. The study aims to study the long‐term virological, immunological and clinical outcomes of PLHIV and to monitor temporal changes and regional differences in outcomes across Europe. Annually collected data include basic demographic characteristics, information on AIDS‐ and non‐AIDS‐related clinical events, and details about antiretroviral therapy (ART), hepatitis C treatment and other medications, in addition to a range of laboratory values. The summer 2016 data set held data from a total of 23 071 individuals contributing 174 481 person‐years of follow‐up, while EuroSIDA's unique plasma repository held over 160 000 samples. Over the past 25 years, close to 300 articles have been published in peer‐reviewed journals (h‐index 52), covering a range of scientific focus areas, including monitoring of clinical and virological outcomes, ART uptake, efficacy and adverse events, the influence of hepatitis virus coinfection, variation in the quality of HIV care and management across settings and regions, and biomarker research. Recognizing that there remain unresolved issues in the clinical care and management of PLHIV in Europe, EuroSIDA was one of the cohorts to found The International Cohort Consortium of Infectious Disease (RESPOND) cohort consortium on infectious diseases in 2017. In celebration of the EuroSIDA study's 25th anniversary, this article aims to summarize key scientific findings and outline current and future scientific focus areas.